Comparison of Temperature Changes Between Holmium-YAG Laser and Thulium Fiber Laser in an In Vitro Setting - Vaibhavkumar Patel; Kshitij Raghuvanshi; Krushnadevsinh Jadeja; Rajeev Chaudhari (Urology Research and Practice)
Objective: We aimed to evaluate and compare the rise in the temperature for the safety of the ureter and kidney parenchyma when firing the holmium laser and the thulium fiber laser (TFL).